2015
DOI: 10.7762/cnr.2015.4.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bioelectrical Impedance Analysis for the Assessment of Nutritional Status in Critically Ill Patients

Abstract: Malnutrition is common in the critically ill patients and known to cause a variety of negative clinical outcomes. However, various conventional methods for nutrition assessment have several limitations. We hypothesized that body composition data, as measured using bioelectrical impedance analysis (BIA), may have a significant role in evaluating nutritional status and predicting clinical outcomes in critically ill patients. We gathered clinical, biochemical, and BIA data from 66 critically ill patients admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 30 publications
6
82
0
7
Order By: Relevance
“…PhA has also been suggested to be a prognostic marker for nutrition status in ICU patients . Accordingly, we showed that inadequate nutrition support in the SC group led to a lower PhA and, thus, to reduced nutrition status.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…PhA has also been suggested to be a prognostic marker for nutrition status in ICU patients . Accordingly, we showed that inadequate nutrition support in the SC group led to a lower PhA and, thus, to reduced nutrition status.…”
Section: Discussionmentioning
confidence: 57%
“…PhA has also been suggested to be a prognostic marker for nutrition status in ICU patients. 21,28 Accordingly, we showed that inadequate nutrition support in the SC group led to a lower PhA and, thus, to reduced nutrition status. In some studies, further relationships have been reported, eg, between PhA and mortality, 22,[29][30][31] or between PhA and length of hospital 22,37 and ICU stay.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Á³îåëåêòðè÷íèé îï³ð ìîaeå âèêîðèñòîâóâàòèñü äëÿ îö³íêè ñêëàäó òêàíèí ò³ëà ³, ïåðåâàaeíî, áåçaeèðîâî¿ ìàñè ò³ëà КЛІНІЧНІ РЕКОМЕНДАЦІЇ / НАСТАНОВИ ó ñòàá³ëüíîãî ïàö³ºíòà, ùî íå ñòðàaeäຠíà ïîðóøåííÿ ð³äèííèõ êîìïàðòìåíò³â [34]. Ó ðÿä³ äîñë³äaeåíü îïèñàí³ ïåðåâàãè á³î³ìïåäàíñó [35][36][37][38] ³ ïåðåâàaeíî ôàçîâîãî êóòà [39] â îö³íö³ ïðîãíîçó äëÿ òÿaeêîõâîðèõ ïàö³ºíò³â. Ïðîòå éîãî çàñòîñóâàííÿ íå º ïîøèðåíîþ ïðàêòèêîþ.…”
Section: ïðèì³òêàunclassified
“…Dnevna kolebanja sadržaja telesne vode uslovljenih unosom hrane, vode i fizičkom aktivnošću [18] mogu imati uticaja na preciznost i tačnost metode. Pouzdanost dobijenih vrednosti zavisi i od drugih faktorapoložaja tela, trajanja merenja, hidriranosti, faze mensturalnog ciklusa kod žena i dr. Metoda ima svoju primenu u različitim populacijama zdravih i bolesnih ljudi, kada se može koristiti i za procenu malnutricije kod kritično obolelih [19,20].…”
Section: Analiza Metodom Bioelektrične Impedance (Bia)unclassified